(untitled) (Cuea Journal of Business and Economics, 2025)
The private security sector emerges as the primary force in protecting individuals together with assets and communities because of the evolving threat environment. The performance of private security firms remains essential in protecting public safety because security threats continuously change while people expect greater services from these organizations. This study examined the influence of on the performance of private security firms in Nairobi County, Kenya. Guided by Schein’s Organizational Culture Theory, Resource-Based View (RBV), Organizational Theory, and Agency Theory, the research employed a descriptive design with data collected from 80 respondents across 30 registered firms through stratified purposive sampling. A semi-structured questionnaire and pilot testing ensured validity and reliability. Performance was evaluated using the Balanced Scorecard (BSC), incorporating financial indicators such as profitability and non-financial measures including service quality, employee satisfaction, reputation, and customer trust. The statistical analysis, conducted using SPSS, revealed strong positive relationships between the core values and organizational performance. Qualitative responses highlighted challenges such as inconsistent application of values, weak leadership, and limited regulatory enforcement, but also proposed employee-driven interventions to strengthen ethical adherence and operational standards. The findings affirm that core organizational values are not only ethical foundations but also critical determinants of operational efficiency, customer trust, and long-term sustainability in the security sector. The study recommends institutionalizing value-based leadership, enhancing training and accountability structures, and establishing stronger regulatory frameworks. These insights contribute to organizational culture literature while offering actionable guidance for managers, policymakers, and future researchers.